Validity Test of Android-Based Learning Media Assisted by Ispring Suite on Pythagorean Theorem Material - Triayuningsih Permata Suci; Sunismi Sunismi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
The development of technology today has a great influence on human life. This influence also includes the use of technology in education, such as the utilization of learning media connected to information technology. This research was conducted to validate the use of learning media in the form of Android applications with the help of iSpring Suite in learning Pythagorean Theorem material. The research method used is RnD by applying the ADDIE model. The research subjects consisted of 3 experts, one practitioner, and 5 grade VIII students. Data collection involved qualitative and quantitative data. The results of the analysis showed that the experts gave an average assessment of 92.09% with the category "Very Valid." Trials conducted on practitioners and small groups also showed a "Very Valid" assessment with an average of 90%. Overall, it can be concluded that the use of Android-based learning media with iSpring Suite is appropriate and effective in achieving learning objectives. With this learning media that has been proven valid and effective, it can be an interesting alternative to improve the quality of mathematics learning in the classroom. Integrating technology in learning can also provide a more interactive and interesting learning experience for students. Thus, the results of this study make a positive contribution to answering the challenges of education in the digital era, enriching learning methods, and increasing the attractiveness of learning materials.